Rich dad's increase your financial IQ : get smarter with your money - Kiyosaki, Robert T., 1947- (AZ, USA : Plata Publishing, 2013)
Emphasizes the importance of financial intelligence to good money management and describes how to improve financial information and increase, protect, budget, and leverage money.
Keywords: Finance, Personal -- Handbooks, manuals, etc